Enabling models of inclusive growth: Addressing the need for financial and social inclusion - HEDRICK-WONG, Yuwa (Institutional Knowledge at Singapore Management University, 2019)
While poverty is falling, the gap between the rich and poor is getting wider and more and more people are being excluded from the means to better themselves. Yuwa Hedrick-Wong and Howard Thomas look at ways to include them.